(untitled) (Journal of Hama University, 2021)
Background: GA has been a useful modality for offering dental treatment to young children with rampant caries and children with special care needs who do not cope well with clinical dental care. However, there is a need to understand the environment of paediatric dentists performing the treatment under GA to provide safe and optimal care. Materials and Methods: the Anaesthetic Theatre Educational Environment Measure ATEEM was utilised to assess the perception of educational atmosphere among postgraduate paediatric dentists performing treatment under GA in the Department of Pediatric Dentistry in Damascus University between 2018-2020. Online Arabic questionnaire designed by Google forms with 40 items, was designed. Results: About 23 postgraduate pediatric students included in the study in which 61% were males and 39% were females. The total mean ATEEM score was 124.14±31.91 indicating that the positive perception towards educational environment. However, a lower score was obtained after answering question 1 (1.08) and question 13 (1.80). The mean score of PAU was 28.30±3.98. The mean score of PAT was 31.26±9.44. The PW/PS was 20.86±5.8. The mean score of PTT was 15.47±5.03. The mean score of PLO was 28.21±9.17. Conclusion: The ATEEM scale provided information about the educational environment for paediatric dental postgraduates who provide dental care under GA, as well as highlighted the gaps and strengths that could be considered in the future to provide a supportive and warm environment for pediatric dental students and ensure safe integrated dental treatment under GA.